The Impact of Tax Morale and Institutional Quality on the Shadow Economy - Benno Torgler; Friedrich Schneider (Center for Research in Economics, Management and the Arts (CREMA), 2007)
This paper analyses how tax morale and countries' institutional quality affect the shadow economy, controlling in a multivariate analysis for a variety of potential factors. The literature strongly emphasizes the quantitative importance of these factors to understand the level and changes of shadow economy. Relatively new available data sources offer the unique opportunity to shed more light in the understanding of a topic that has received an increased attention. We find strong support that a higher tax morale and a higher institutional quality lead to a smaller shadow economy.
Keywords: D73; D78; H2; H26; O17; O5; 330; Shadow economy; tax morale; institutional quality; government intervention; corruption